Efeitos anti-nociceptivo e anti-edematogênico da glibenclamida em um modelo de gota aguda em ratos - Santos, Rosane Maria Souza dos (2013)
Gout is one form of inflammatory arthritis, which is caused by the precipitation of crystals of monosodium urate (MSU) in the joints. Acute gout is associated with sudden and painful inflammatory episodes characterized by high neutrophil infiltration. In spite of years of study gout treatment remains a challenge due to its relative ineficcacy. Thus, search for new and efficient therapies is necessary. The objective of this study was to investigate the involvement of glibenclamide in a model of acute gout in rats induced by MSU. MSU crystals produced nociception and edema when injected into the ankle joint of rats. Treatment with glibenclamide (3 mg/kg, s.c.) or dexamethasone (8 mg/kg, s.c., used as a positive control) decreased spontaneous nociception (67% ± 11 and 70 ± 7% inhibition, respectively) and edema (28 ± 7% and 77 ± 7% inhibition, respectively) induced 6 hours after MSU injection. The number of leukocyte infiltrates in the synovial fluid as well as the release of interleukin 1β (IL-1β) and prostaglandin E2 (PGE2) significantly increased at 6 hours after injection of MSU joint, but these effects were not reversed by treatment with glibenclamide (3 mg/kg, s.c.). In contrast, dexamethasone reduced the leukocyte infiltration and release of IL-1β and PGE2. To confirm if the dose of glibenclamide was able to block the KATP channels, we determined the levels of glucose in the blood of animals. Glibenclamide decreased (23 ± 2%) and dexamethasone increased the blood glucose of the rats compared to vehicle-treated animals / MSU. Therefoe, the effects of glibenclamide on nociception and edema induced MSU, suggests that this sulfonylurea may be an interesting option as an adjunct therapy in pain observed in acute attacks of gout.